Evaluasi Dampak Program Keluarga Harapan Terhadap Pemanfaatan Fasilitas Pelayanan Kesehatan untuk Layanan Persalinan di Indonesia (Analisis Data SUSENAS tahun 2018) - Putra, Gede Wirabuana; Pujianto, Pujianto (UI Scholars Hub, 2020)
Program Keluarga Harapan (PKH) aims to improve the standard of living of the people as measured through the Human Development Index (IPM) and the level of inequality in expenditure of the Indonesian population (Gini Ratio) by accommodating the utilization of health services as one of the indicator. In 2018 there are still 16% of deliveries that were not performed by trained health workers at healthcare facilities. One health component that is required as a PKH Beneficiary Family (KPM) is that pregnant women are required to deliver in a health care facility. The purpose of this study is to look at the effect of PKH on the use of health facilities for childbirth in Indonesia.The Methods that used in this study is a quasi-experimental with cross sectional design using Susenas data in 2018 with a total sample of 28,785 mothers aged 15-49 years who had given birth to live births in the period of two years before the survey and economic status in deciles 1-3. The analysis uses the Propensity Score Matching (PSM) method with the Logit model that looks at the OR value. The Results is PKH increased maternity utilization in health facilities. PKH recipients have a 1.23 times higher chance than non-PKH recipients, after controlling for other variables. PKH implementation has quite good benefits, along with other dominant supporting factors, namely the area of residence, education, communication tools, transportation facilities and JKN-PBI in order to help the community, especially the poor and vulnerable, to utilize health care facilities for delivery.